The Materiality of the Horse in Iron Age and Historical Finland as observed in Zooarchaeological and Folk-Belief Material - Bläuer Auli; Hukantaival Sonja; Kantanen Juha (Trivent Publishing, 2022)
In this article, we combine zooarchaeological, ethnological and folk-belief material to study the deposition of archaeological horse remains and the beliefs and symbolic or social attributes associated with horses. We collected zooarchaeological data from 58 Iron Age, medieval and post-medieval archaeological sites and studied abundance of horse remains, their anatomical distribution and their archaeological context. From the nineteenth to the early twentieth century, horses were considered apart from other farm animals and were thought to possess special abilities, such as sensing otherworldly activity. The understanding of the complex traditions, beliefs and practices affecting the material remains of horses is aided by the large dataset spanning a long period, careful consideration of find contexts, and the anatomical distribution and multisource approach.